Experimental evaluation on the performance of waste biomass briquettes formation and combustion characteristics - Law, Hoon Chit (2017)
In the twentieth century, biomass energy has received tremendous attention for the waste biomass to be recognised as a renewable and profitable energy carrier. Malaysia is conducting intensive agricultural practices whereby around 150 billion metric tonnes of agricultural wastes are generated annually. This vast amount of biomass residues could be processed as energy source because its use will not only interfere with traditional agricultural practices or jeopardize the food security, but instead further enhances them. However, wide diversity of physical size and shapes, compositions and energy densities among different agricultural biomass posed challenges in handling, storage, feeding as well as transportation. Biomass briquetting therefore is implemented to compact the residues into a high bulk density pellet, briquette or cube by densification. However, some of the residues could not be briquetted and other alternatives, for example, addition of a binder or mixing of biomass materials are required. The main objective of this research is to study the potential and how the selected biomass could be used as a renewable source effectively in solid fuel production. On top of that, the mechanical and combustion properties of the briquettes would be investigated accordingly. In this study, rice husk, sugarcane bagasse and spent coffee ground were chosen as the biomass feedstock for briquette formation. The collected biomass residues were reduced in size after the dehumidification process. After that, the briquetting facility was specifically designed to accommodate the doughnut-shaped briquette formation. In the first set of experiment, the effects of the variation of preheating temperature (120, 150 and 180°C), compacting pressure (200, 250 and 300 bars) and the biomass type (rice husk, sugarcane bagasse and spent coffee ground) on the shatter resistance, abrasive resistance, water resistance and compressive resistance of the densified product were investigated. It was found that the shatter resistance increased with pressure and temperature to around 92.09-100%. The abrasive resistance increased from 83.25-90.15% to 99.74-99.79% except sugarcane bagasse briquette which was stable at 100%. Besides, 3.26-36.56% of increment was recorded in the water resistance with the increasing pressure and temperature. The compressive resistance, on the other hand increased to 236.29-1077.78 N. The result also showed that the sugarcane bagasse briquettes exhibited higher strength as compared to that of rice husk and spent coffee ground briquettes, however, spent coffee ground briquettes showed the highest water resistance capability. In the second set of experiments, three types of biomass blend briquettes had been formed: rice husk and sugarcane bagasse, rice husk and spent coffee ground, sugarcane bagasse and spent coffee ground with the mixing ratio of 80:20, 60:40, 40:60 and 20:80. The optimum processing parameters used in this experiment were 150°C and 300 bars. The mechanical properties of the blend briquettes were analysed with respect to the blend ratio and the high heating value, ultimate analysis and water boiling test were conducted to evaluate the performance of the briquettes. The result shows that the briquette containing rice husk and sugarcane bagasse (weight ratio 20:80), rice husk and spent coffee ground (20:80) and sugarcane bagasse and spent coffee ground (40:60) exhibits the mechanical strength and combustion performance which can fulfill the acceptance limit as well as the minimum requirement as a commercial briquette. In conclusion, the experimental results verified the effectiveness of methods applied in this research in biomass briquetting to improve the mechanical strength and durability as well as the calorific value and combustion rate of the briquettes. Mixing of biomass can be the other alternative solution for the industry other than using only one type of residues such as palm wastes and wood residues in solid fuel formation for energy generation. This research thus provides the insights of the mechanical and combustion properties for different biomass briquettes, contributing to further benefits of the application of agricultural biomass to enhance solid fuel conversion.